EUROPEAN UNION AT THE DAWN OF TECHNOLOGICAL COLD WAR - Gajewski, Tomasz (Torun International Studies, 2023)
The purpose of the study was to construct a picture of the EU’s global position in a world defined by the US-Chinese technological Cold War. Morphological analysis has been used to enable a comprehensive analysis of the relationship between the technological and social domains. Structured interviews were also used to support the analytical process. The results of the exploration showed a picture of the EU’s multi-level technological weakness compared to competing powers. While the EU is not a weak entity, its future international position will depend on the creation of its own technological capabilities and on cooperation with the United States. Both lines of action are subject to multiple risks. Firstly, some aggressive technological developments (such as the plans to place microchips production in Europe) can generate more problems than diversification. Secondly, the EU must extend its work on high-tech (primarily AI) beyond the logic of market regulation and focus on their geopolitical and military dimension. It must also be ready for possible obstacles in cooperation with the United States. The alternative to this track, as the analysis shows, is the technological, and hence the political and economic peripheral status, where two technological superpowers – the United States and authoritarian China will compete. The most negative result for the EU is the status of “digital colony”. The paper aspires to be a part of the effort to fill the existing void in the scientific output of Polish social sciences, regarding exploration of the geopolitical dimension of technological progress, especially its impact on EU’s position in the new power distribution model, which will be the result of the rivalry between the US and China.